Severe Psychosis, Drug Dependence, and Hepatitis C Related to Slamming Mephedrone - Helen Dolengevich-Segal; Beatriz Rodríguez-Salgado; Jorge Gómez-Arnau; Daniel Sánchez-Mateos (Case Reports in Psychiatry)
Background. Synthetic cathinones (SCs), also known as “bath salts,” are β-ketone amphetamine compounds derived from cathinone, a psychoactive substance found in Catha edulis. Mephedrone is the most representative SC. Slamming is the term used for the intravenous injection of these substances in the context of chemsex parties, in order to enhance sex experiences. Using IV mephedrone may lead to diverse medical and psychiatric complications like psychosis, aggressive behavior, and suicide ideation. Case. We report the case of a 25-year-old man admitted into a psychiatric unit, presenting with psychotic symptoms after slamming mephedrone almost every weekend for the last 4 months. He presents paranoid delusions, intense anxiety, and visual and kinesthetic hallucinations. He also shows intense craving, compulsive drug use, general malaise, and weakness. After four weeks of admission and antipsychotic treatment, delusions completely disappear. The patient is reinfected with hepatitis C. Discussion. Psychiatric and medical conditions related to chemsex and slamming have been reported in several European cities, but not in Spain. Psychotic symptoms have been associated with mephedrone and other SCs’ consumption, with the IV route being prone to produce more severe symptomatology and addictive conducts. In the case we report, paranoid psychosis, addiction, and medical complications are described.